The role of perioperative chemoimmunotherapy in the treatment of potentially resectable MSI-H gastric adenocarcinoma - a case report - Sokop, T; Kysela, M; Sládek, F; Lordick Obermannová, R (Rozhledy v chirurgii, 2024)
INTRODUCTION: Gastric and gastroesophageal junction adenocarcinoma is a disease with high mortality. Approximately 10% of these tumors are characterized by microsatellite instability with a presumed good response to immunotherapy. So far, treatment with checkpoint inhibitors is part of palliative regimens, in the Czech Republic this treat-ment is reimbursed in patients with MSI-H gastroesophageal adenocarcinoma exhibiting a combined positive score ≥ 5. Promising results of immunotherapy used in the early stages of MSI-H gastroesophageal adenocarcinoma were published recently. CASE REPORT: A 59-year-old woman with locally advanced poorly cohesive MSI-H adenocarcinoma of the small curvature of the stomach. Based on the indication of the multidisciplinary team, she started neoadjuvant treatment with chemoimmunotherapy. The outcome was significant partial regression of the primary tumor and infiltrated gastric lymph nodes. Subsequently, the patient underwent uncomplicated radical total gas-trectomy with D2 lymphadenectomy. After a short postoperative recovery, she continues adjuvant treatment with immunotherapy, so far with good tolerance. CONCLUSION: This case report supports the potential importance of immunotherapy in the treatment of resectable locally advanced MSI-H gastric cancer, which is currently being evaluated in clinical trials.
Keywords: nádory žaludku; Adenocarcinoma; neoadjuvantní terapie; Humans; mikrosatelitní nestabilita; lidé středního věku; Microsatellite Instability; Female; protokoly protinádorové kombinované chemoterapie; immune checkpoint inhibitors; lidé; Immunotherapy; immunotherapy; ženské pohlaví; microsatellite instability; Middle Aged; perioperative treatment; Antineoplastic Combined Chemotherapy Protocols; Neoadjuvant Therapy; adenokarcinom; gastroesophageal adenocarcinoma; immunotherapy; imunoterapie; Stomach Neoplasms